2011
DOI: 10.1111/j.1399-5618.2011.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

The co‐occurrence of cigarette smoking and bipolar disorder: phenomenology and treatment considerations

Abstract: Objectives Despite recent advances in understanding the causes and treatment of nicotine dependence among individuals with psychiatric disorders, smoking among individuals with bipolar disorder (BD) has received little attention. The goal of this review is to synthesize the literature on the epidemiology, consequences, and treatment of smoking and nicotine dependence among individuals with BD and to delineate a future research agenda. Methods We conducted a PubMed search of English-language articles using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 129 publications
1
88
1
6
Order By: Relevance
“…We had only indirect information on heavy smoking, which is an established risk factor for both renal cancer and cancers of the pelvis or ureter. 28 Individuals suffering from bipolar disorder and severe depression, including lithium users, smoke on average more than the general population, 29,30 and thus smoking might have confounded the risk estimates in our study. However, any confounding by smoking would result in an overestimation of the association between lithium use and UUTC risk, and thus our finding of mainly neutral associations between lithium use and UUTC risk provides further reassurance of our null results.…”
Section: Discussionmentioning
confidence: 90%
“…We had only indirect information on heavy smoking, which is an established risk factor for both renal cancer and cancers of the pelvis or ureter. 28 Individuals suffering from bipolar disorder and severe depression, including lithium users, smoke on average more than the general population, 29,30 and thus smoking might have confounded the risk estimates in our study. However, any confounding by smoking would result in an overestimation of the association between lithium use and UUTC risk, and thus our finding of mainly neutral associations between lithium use and UUTC risk provides further reassurance of our null results.…”
Section: Discussionmentioning
confidence: 90%
“…Do psychiatrists even recognize counseling about smoking cessation (alongside other lifestyle factors that jeopardize physical health and longevity) as falling within their purview and scope of practice? An extensive review 8 of cigarette smoking and bipolar disorder observed that, while most surveyed psychiatrists were aware of smoking status among their patients, counseling or intervention was provided during no more than 12% of visits. This marked disparity is especially troubling given the relevance of smoking to mental health management, including known links between smoking and depression, smoking and other substance misuse, the need to gauge metabolic risk factors when prescribing medications that can adversely affect weight or glycemic and lipid levels, and, not least of all, anticipating pharmacokinetic interactions between tobacco smoke and certain antipsychotics or serotonin reuptake inhibitors.…”
Section: Joseph F Goldberg MDmentioning
confidence: 99%
“…This marked disparity is especially troubling given the relevance of smoking to mental health management, including known links between smoking and depression, smoking and other substance misuse, the need to gauge metabolic risk factors when prescribing medications that can adversely affect weight or glycemic and lipid levels, and, not least of all, anticipating pharmacokinetic interactions between tobacco smoke and certain antipsychotics or serotonin reuptake inhibitors. 8 Second, psychiatrists must feel knowledgeably equipped to guide their patients as well as other physicians and health care providers about the psychiatric safety of varenicline as a treatment option for smokers with psychiatric illnesses. How do we place into proper context the handful of case reports linking varenicline with iatrogenic psychosis or adverse mood effects alongside the US Food and Drug Administration's 2009 black box warning of an 8-fold increased risk for suicidal or self-injurious behavior?…”
Section: Joseph F Goldberg MDmentioning
confidence: 99%
See 1 more Smart Citation
“…The nicotine addiction and the tobacco smoking have an high prevalence in schizophrenia and bipolar disorders [47,48]. In the bipolar disorder peoples, tobacco smoking is prevalent [49].…”
Section: Human and Epidemiological Evidencesmentioning
confidence: 99%